Efektivitas Peraturan Daerah Kota Jambi Nomor 2 Tahun 2014 dalam Pemberantasan Pelacuran dan Perbuatan Asusila di Wilayah Kota Jambi - Badri, Mhd.; Sumaidi, Sumaidi; Iswanto, Reza (Universitas Batanghari Jambi, 2024)
The occurrence of criminal acts of prostitution and immoral acts in the city of Jambi is currently widespread. This can also be proven by the existence of cases of prostitution at OYO accommodation located in the city of Jambi. Even though there is Jambi City Regional Regulation Number 2 of 2014 on the Eradication of Prostitution and Immoral Acts, in reality there is still prostitution in the city of Jambi even though the local area has been closed. The aim of this research is to understand and analyze the factors that influence people to commit prostitution and immoral acts in Jambi City, obstacles in implementing the effectiveness of Jambi City Regional Regulation Number 2 of 2014 in Eradicating Prostitution and Immoral Acts in the Jambi City area and efforts to overcome obstacles in reducing the number of prostitution and immoral acts in the Jambi city area. The research method is an empirical juridical research type with a legal sociology approach and uses data sources, namely primary legal materials and secondary legal materials. The sampling technique was purposeful sampling and data collection techniques were carried out using interviews and document studies and data analysis was carried out using qualitative analysis. The results of his research are that the factors that influence people to commit prostitution and immoral acts in Jambi City are economic and lifestyle factors, a profitable prostitution business, teenagers having broken home family backgrounds and joining the wrong social groups, the existence of hotels and nightclubs or club. The obstacle in carrying out the effectiveness of Jambi City Regional Regulation Number 2 of 2014 in Eradicating Prostitution and Immoral Acts in the Jambi city area is that criminal sanctions are categorized as light and not as a coercive tool to ensnare perpetrators of prostitution, there is no special authority for the police to carry out criminal sanctions in the Regional Regulation. , there was a leak of information during the raid, the condition of the Youth and Women's Social Home in Talang Bakung was still worrying as it could become a rehabilitation place for prostitutes, there was resistance from the community around the prostitution localization to close the prostitution localization, there was foreign culture coming in such as promiscuity. An effort to overcome obstacles in reducing the number of prostitution and immoral acts in the Jambi city area is that the Jambi City Government closes down the localization of prostitution in the city of Jambi, then carries out socialization of Regional Regulation Number 2 of 2014 to the people of Jambi city, the Jambi city government and the Jambi City Civil Service Police Unit. coordinating with the TNI and Polri in carrying out raids as well as the role of the community or parents in supervising their children when using cellphones.